“Wasathiyah” atau “Moderasi”? Mencari Dasar Pemersatu dalam Peradaban Islam - Damyati, Akhmad Rofii (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2021)
This article is intended to study the conceptual meaning of two terms which are nowadays trending among people, especially Indonesian People, that are, “wasathiyyah” from Quranic terminology and “moderation” from Western tradition, by analysing their semantic fields and meanings. It aims to make clear which one is more reliable for unity of this ummah as a reference in the context of Islamic civilization. As a result of the discussion, “wasathiyyah” is best used to articulate the moderation in Islam because of the contents of its meaning are more complex and complete as compared to moderate and more rebiable to used in the context of Islamic civilization